Effect of Endogenous and Exogenous Butyric Acid on Butanol Production From CO by Enriched Clostridia - He, Yaxue; Lens, Piet N. L.; Veiga, María C.; Kennes, Christian (Frontiers in Bioengineering and Biotechnology, 2022)
Butanol is a potential renewable fuel. To increase the selectivity for butanol during CO fermentation, exogenous acetic acid and ethanol, exogenous butyric acid or endogenous butyric acid from glucose fermentation have been investigated using CO as reducing power, with a highly enriched Clostridium sludge. Addition of 3.2 g/L exogenous butyric acid led to the highest 1.9 g/L butanol concentration with a conversion efficiency of 67%. With exogenous acetate and ethanol supply, butanol concentration reached 1.6 g/L at the end of the incubation. However, the presence of acetic acid and ethanol favoured butanol production to 2.6 g/L from exogenous butyric acid by the enriched sludge. Finally, exogenous 14 g/L butyric acid yielded the highest butanol production of 3.4 g/L, which was also among the highest butanol concentration from CO/syngas fermentation reported so far. CO addition triggered butanol production from endogenous butyric acid (produced from glucose, Glucose+N2) with as high as 58.6% conversion efficiency and 62.1% butanol yield. However, no efficient butanol production was found from glucose and CO co-fermentation (Glucose+CO), although a similar amount of endogenous butyric acid was produced compared to Glucose+N2. The Clostridium genus occupied a relative abundance as high as 82% from the initial inoculum, while the Clostridia and Bacilli classes were both enriched and dominated in Glucose+N2 and Glucose+CO incubations. This study shows that the supply of butyric acid is a possible strategy for enhancing butanol production by CO fed anaerobic sludge, either via exogenous butyric acid, or via endogenous production by sugar fermentation.